2010
DOI: 10.1258/msl.2009.009017
|View full text |Cite
|
Sign up to set email alerts
|

The use of Section 136 (Mental Health Act 1983) in Gloucestershire

Abstract: The small number of published studies on the use of Section 136 (S136) of the Mental Health Act 1983 may reflect neither the current situation nor the true national picture as most of the research comes from large urban centres and was published before 1997. We studied the use of S136 between 2002 and 2006 in Gloucestershire, a rural English county with a population of approximately 585,000, by analysing data held by the police and local mental health services. On average 192 subjects (range 176-203) were deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…One highly pertinent issue that has been highlighted by several studies is that S136 is closely tied to suicide prevention. Estimates place between 55% and 81% of detentions as being linked to concerns about the detained person’s risk to their own life rather than to the threat of harming others [11,12]. A recent comprehensive study investigating the use of S136 in the adjacent counties of East and West Sussex revealed many important elements involved in the historically high rates of detention seen within that area of South East England [13].…”
Section: Introductionmentioning
confidence: 99%
“…One highly pertinent issue that has been highlighted by several studies is that S136 is closely tied to suicide prevention. Estimates place between 55% and 81% of detentions as being linked to concerns about the detained person’s risk to their own life rather than to the threat of harming others [11,12]. A recent comprehensive study investigating the use of S136 in the adjacent counties of East and West Sussex revealed many important elements involved in the historically high rates of detention seen within that area of South East England [13].…”
Section: Introductionmentioning
confidence: 99%
“…One highly pertinent issue that has been highlighted by several studies is that S136 is closely tied to suicide prevention. Estimates place between 55% and 81% of detentions as being linked to concerns about the detained person's risk to their own life rather than to the threat of harming others [11,12]. A recent comprehensive study investigating the use of S136 in the adjacent South East England counties of East and West Sussex revealed many important elements involved in the historically high rates of detention seen within that area [13].…”
Section: Introductionmentioning
confidence: 99%
“…The study covers London only, which may not be representative of other areas. Indeed, other commentators have been critical of this reliance on London to describe the Section 136 process (Borschmann et al, 2010;Laidlaw et al, 2010). The study was conducted prior to the introduction of the roll-out of street triage schemes, and although some interviews were undertaken with workers, they did not explain adequately how this service could address the issues raised in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, commentators have been critical of the police's approach to managing people in mental health crisis due to a lack of understanding of an individual's mental health needs (McDaniel, 2019;Independent Commission on Mental Health and Policing, 2013;Clifford, 2010). Studies of detainee perspectives have highlighted the traumatic nature of the detention process, which has resulted in dissatisfaction with both police and health professionals (McGuinness, Dowling, & Trimble, 2013;Laidlaw, Pugh, Riley, & Hovey, 2010;Jones & Mason, 2002). For mental health services, there is an evidence base that largely focuses on treatment and approaches within a ward context once a person is admitted as an inpatient (Slemon, Jenkins, & Bungay, 2017).…”
Section: Introductionmentioning
confidence: 99%